TORQUE360: Expanding a Woman-run Business - Anum, Kamna; Abdul Hamid, Abu Bakar; Ishaq Kureshi, Nadeem (IIUM Journal of Case Studies in Management, 2022)
From a hopeless Human Resource Manager to an active Blogger and then from a Blogger to a successful entrepreneur, Saadia’s journey is a perfect example “live your dreams”. In order to utilize her technical, non-technical and managerial skills, she always wanted to run a successful consultancy firm. At initial stages, she started providing marketing assistance to some of her national and international social media marketing clients. Within a month, she managed to offer various consultancy services (Enterprise Management, Marketing and Advertisement, Information Technology and Human Resource Management). Saadia was now planning to expand her virtual business by establishing her first traditional office setup in Lahore. But, at the same time, she wondered how she would manage to run a traditional setup and, most importantly, whether it would be a good idea to expand a Virtual Business Consultancy Firm to a Traditional office setup. This case study is designed to teach some important Management Sciences and Business concepts. Learning outcomes include: small and medium enterprise management, women entrepreneurship, Virtual/traditional business expansion and its pros & cons.